1976
DOI: 10.1002/eji.1830060513
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Ig on human lymphocytes: rate of turnover of IgD and IgM on the surface of human tonsil cells

Abstract: The turnover of IgM and IgD molecules present on the membrane of human tonsil cells has been studied using immunofluorescence and peroxidase-catalyzed membrane radioiodination. With the first of the two techniques cells were treated with pronase to remove membrane immunoglobulin (mIg), placed in culture and stained at intervals to check the reappearance of membrane IgD and IgM on the cell membrane. These experiments showed that membrane IgD (in contrast to membrane IgM) are extremely susceptible to proteolysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0

Year Published

1977
1977
2002
2002

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 25 publications
(7 reference statements)
2
15
0
Order By: Relevance
“…These results are consistent with the reports of other investigators that surface IgD, in contrast to surface IgM, is extremely susceptible to proteolysis (30,31 The phenomenon of loss of surface IgD from B cells has been described by several investigators to occur after stimulation of mature B cells by mitogens or antigens and is presumably the result of differentiation of B cells, which later become IgM-, IgG-, and IgA-secreting cells (20). In several recent studies, researchers have shown that spleen lymphocytes in NZB mice have markedly decreased levels of surface IgD relative to IgM (3,4,33).…”
Section: Discussionsupporting
confidence: 94%
“…These results are consistent with the reports of other investigators that surface IgD, in contrast to surface IgM, is extremely susceptible to proteolysis (30,31 The phenomenon of loss of surface IgD from B cells has been described by several investigators to occur after stimulation of mature B cells by mitogens or antigens and is presumably the result of differentiation of B cells, which later become IgM-, IgG-, and IgA-secreting cells (20). In several recent studies, researchers have shown that spleen lymphocytes in NZB mice have markedly decreased levels of surface IgD relative to IgM (3,4,33).…”
Section: Discussionsupporting
confidence: 94%
“…Previously, Finkelman et al [3] reported identical elec trophoretic mobilities in SDS-PAGE of hu man cellbound //-and ¿-chains. In contrast, Ferrarini et al [2] found slower mobilities for both cell-bound //-and ¿-chains com pared to their scrum Ig counterparts. In these experiments, the differences in mobili ty between cell-bound and secreted heavy chains were small, and although they were reproducible, only structural evidence will establish that cell-bound heavy chains are larger than the heavy chains of the secreted…”
Section: Discussionmentioning
confidence: 88%
“…catarrhalis is the third most frequent cause of bacterial otitis media and therefore is a major cause of disease. Significant numbers of normal IgD-secreting plasma cells have been found in human bronchus-associated lymphoid tissue and tonsils (4,5). This has been suggested to be due to the fact that the upper respiratory tract in humans is frequently colonized by strains of H. influenzae and M. catarrhalis, which exposes membrane proteins that activate IgD ϩ B lymphocytes (7).…”
Section: Discussionmentioning
confidence: 99%
“…IgD has been suggested to be involved in peripheral B cell tolerance, B cell recruitment, and secondary Ig light chain rearrangement, i.e., receptor editing, but still much of the function of IgD remains to be solved (1)(2)(3). Only trace amounts of IgD are found in serum, but significant numbers of normal IgD-secreting plasma cells have been found in human bronchus-associated lymphoid tissue and tonsils (4,5). This observation might be linked to the fact that the upper respiratory tract in humans are frequently colonized by strains of Moraxella catarrhalis and Haemophilus influenzae, which express outer membrane surface proteins that activate IgD ϩ B lymphocytes by cross-linking IgD (6,7).…”
mentioning
confidence: 99%